HeLa cell line, a model to study the role of cofactor of BRCA1 in cervical cancer - Abd Elhamied, Noha Saad (AUC Knowledge Fountain, 2018)
Being one of the four subunits that makes up the Negative Elongation Factor Complex (NELF), Cofactor of BRCA1 (COBRA1); also known as NELF-B, is able to regulate a number of genes involved in cellular proliferation, metabolism, cell cycle progression and DNA repair. In addition, COBRA1 was shown to interact with other transcription factors such as BRCA1, AP-1 complex and several nuclear receptors. Despite the evidences that suggest COBRA1 as a potential player involved in the progression of a number of cancers, its role in cervical cancer has not been previously investigated. To date, it has been studied in breast, upper gastrointestinal and liver cancers. The main objective of our study was to investigate the potential involvement of COBRA1 in cervical cancer progression. We first did in-silico analysis of the expression patterns of COBRA1 in cervical cancer tissues relative to normal cervical tissues using the publicly available Oncomine Cancer Microarray Database. Search results revealed a significant upregulation of COBRA1 in two mRNA microarray datasets. RNA interference technique was then used to knockdown COBRA1 expression in cervical cancer cell line, HeLa. Once a successful siRNA mediated silencing at the RNA and protein levels of COBRA1 was established and confirmed through semi-quantitative Reverse Transcription Polymerase Chain Reaction (RT-PCR) and Western Blot, we investigated its consequences on proliferation, migration and survival of HeLa cells. Interestingly, COBRA1 depletion resulted in a significant increase in the mRNA expression of Trefoil Factor 1 (TFF1) accompanied by a subsequent decrease in the Î²-catenin mRNA levels. These findings suggests an effect for COBRA1 on the Wnt/Î²-catenin signalling pathway, which could be mediated through TFF1. In addition, COBRA1 silencing resulted in significant decrease in the expression of survivin 2B and survivin DeltaEX3 isoforms while the observed decrease in survivin wild type form was found to be statistically insignificant. Survivin is known to play a major role in cancer cells proliferation and survival. Yet, the finding that the noted decrease in Î²-catenin and survivin expression was not reflected on the proliferation and migration abilities of HeLa is not conclusive and requires further investigations. Taken together, these findings could help as an initial step in identifying the role of COBRA1 in cervical cancer tumorigenesis.